Growth Response of Peppermint (Mentha piperita L.) Stem Cuttings on Several Composition of Planting Media - Butar Butar, Rio Ramadhan; Sitepu, Ferry Ezra; Hasanah, Yaya (Indonesian Journal of Agricultural Research, 2018)
Planting media is one of the keys to success in cultivating peppermint to produce the optimal growth. The objective of the research is to determine the growth response of peppermint stem cutting on composition of planting media. The research was conducted at the research field of the Faculty of Agriculture, Universitas Sumatera Utara, Medan on August to October 2017 using non factorial randomized block design consisted of composition of planting media (top soil ; top soil + biochar (3:1); top soil + chicken manure (3:1); top soil + empty fruit bunches of palm oil compost (3:1); top soil + empty fruit bunches of palm oil compost + chicken manure (2:1:1); top soil + biochar + chicken manure (2:1:1); top soil + biochar + empty fruit bunches of palm oil compost (2:1:1). The results show that the composition of planting media was significantly effect of the percentage of cutting grows, number of shoots, length of shoots, root volume and number of leaves. Top soil: EFB of palm oil (3: 1) the best treatment because it increases the percentage of cutting growth, root volume, dry weight and root dry weight.